Penguatan Peran Dinas Koperasi dalam Pengawasan untuk Meningkatkan Kinerja Koperasi di Kota Surabaya - Santya, Vandera Marsya; Kustini, Kustini (Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the effectiveness of community service programs that focus on cooperative empowerment in Surabaya, an important city in East Java with a strategic role in the Indonesian economy. Considering that cooperatives in Surabaya often experience management constraints and limited access to finance, this program is designed to overcome these challenges through improving management skills, financial literacy, and technology integration. The methodology of this research involves an initial survey, Focus Group Discussion (FGD) with cooperative stakeholders, and the implementation of a technology-based cooperative management system that aims to increase transparency and operational efficiency. The results of this service activity show a significant increase in the economic and operational capacity of cooperatives. Operational efficiency has increased with a reduction in administration time from six days to 2.5 days. The cooperative's monthly income increased by 50%, from IDR 50 million to IDR 75 million, and new members increased by 46%, indicating an increase in public trust in the cooperative. This program not only improves the performance of cooperatives but also strengthens their role in the local economy through increased market access and business sustainability. These findings imply that cooperative empowerment through managerial capacity development, financial literacy, and the application of technology can effectively improve cooperative performance and competitiveness. Therefore, this program has the potential to be used as a model for sustainable cooperative development in Indonesia. The study also recommends increased training in advanced technologies and infrastructure to support the implementation of effective strategies.